Effects of estrous cycle and xenoestrogens expositions on mice nitric oxide producing system - Gotti, Stefano; Martini, Mariangela; Viglietti-Panzica, Carla; Miceli, Desiree; Panzica, GianCarlo (Italian Journal of Anatomy and Embryology, 2010)
Nitric oxide (NO)containing neurons are widely distributed within the central nervous system, including regions involved in the control of reproduction and sexual behavior. Nitrergic neurons may co-localize with gonadal hormone receptors and gonadal hormones may influence neuronal NO synthase expression in adulhood as well as during development. In rodents, the female, in physiological conditions, is exposed to shortterm changes of gonadal hormones levels (estrous cycle). Our studies, performed in mouse hypothalamic and limbic systems, reveal that the expression of neuronal NO synthase may vary according to the rapid variations of hormonal levels that take place during the estrous cycle. This is in accordance with the hypothesis that gonadal hormone activation of NO-cGMP pathway is important for mating behavior. NO-producing system appears particularly sensitive to alterations of endocrine balance during development, as demonstrated by our experiments utilizing perinatal exposure to bisphenol A, an endocrine disrupting chemical. In fact, significant effects were detected in adulthood in the medial preoptic nucleus and in the ventromedial subdivision of the bed nucleus of the stria terminalis. Therefore, alteration of the neuronal NO synthase expression may be one of the causes of the important behavioral alterations observed in bisphenol-exposed animals.